SATISFACTION LEVELS OF IPB UNDERGRADUATE STUDENTS TOWARD ONLINE LEARNING SERVICES DURING THE COVID-19 PANDEMIC - Nadya Ameylda; Moh. Djemdjem Djamaludin (Journal of Child, Family, and Consumer Studies, 2022)
The Covid-19 pandemic has forced all educational institutions' teaching and learning processes to change the method to be online. Bogor Agricultural University (IPB) is one of the universities that has participated in implementing online learning starting from March 2020. This study aims to analyze the effect of service quality, customer satisfaction, and net benefit. This research belongs to the type of explanatory research through surveys. Respondents in this study were selected using a voluntary sampling technique with 255 respondents. Data was collected through an online questionnaire using a google form. The data obtained were processed using Microsoft Excel, SPSS version 25, and SMART-PLS 3. The results of the descriptive analysis show that, in general, students are satisfied with the service during the implementation of online learning. Half of the students fall into the category of low net benefits. The influence test results show that service quality had a significant positive effect on customer satisfaction, and customer satisfaction had a significant positive effect on net benefits. Suggestions that can be given are that IPB, lecturers, and departmental staff need to maintain and improve the quality of online learning services from various aspects.